Analisis Forensik Keamanan Data Pribadi pada Mode Privasi Browser Menggunakan Metode National Institute of Standards and Technology (NIST) - Syukri, Muhammad; Imam Riadi; Tole Sutikno (Jurnal PROCESSOR, 2025)
User privacy while browsing the internet has become a major concern, especially with the presence of the private mode feature in browsers, which is claimed to protect personal data. This study analyzes the extent to which private mode in Google Chrome and Mozilla Firefox browsers can safeguard personal data using the standard approach from the National Institute of Standards and Technology (NIST). Four simulation scenarios were conducted to evaluate the effectiveness of private mode in preventing user information from being stored. The research findings indicate that although private mode successfully prevents the storage of browsing history and user data on the hard disk, sensitive information such as accounts and passwords can still be accessed in memory (RAM) under certain conditions. These findings suggest that private mode is not entirely secure in protecting user privacy, particularly against attacks that exploit temporary data in RAM. The implications of this study highlight the need for further development in private mode security, both by browser developers and users who seek to enhance their personal data protection. This study also recommends additional strategies to be implemented more effectively in order to reduce the risk of data leakage when using private mode.